Medieval Indian History and Kannada Literary Heritage: A Civilizational Interface - Maleppa Ganiger (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This paper explores the dynamic intersection between Medieval Indian History and the evolution of Kannada literary heritage. The medieval period, stretching from the 8th to the 18th century, witnessed profound political changes, cultural negotiations, and intellectual transformations. These developments shaped regional identities across the subcontinent, particularly in Karnataka. The paper analyses how political structures, religious movements, and socio-economic patterns—especially under the Rashtrakutas, Chalukyas, Hoysalas, and Vijayanagara rulers—contributed to the growth of Kannada literature, including the Vachana, courtly epics, Dasa Sahitya, and classical poetic traditions.